Electron density modulation of Fe1-xCoxP nanosheet arrays by iron incorporation for highly efficient water splitting. (January 2020) - Feng, Haopeng; Tang, Lin; Zeng, Guangming; Yu, Jiangfang; Deng, Yaocheng; Zhou, Yaoyu; Wang, Jingjing; Feng, Chengyang; Luo, Ting; Shao, Binbin
Abstract: The good performance of base metal phosphides as alternative catalysts for hydrogen evolution has attracted great attention. However, phosphorus-hydrogen bonds (P-Hads ) are easily formed on the surface of metal phosphides, which will severely inhibit hydrogen evolution reaction (HER). Herein, we propose a universal strategy to improve the HER activity of metal phosphides by modulating the surface electron densities. The iron modulated Fe0.29 Co0.71 P nanosheet arrays exhibit an overpotential of 74 mV at 10 mA cm −2 and a Tafel slope of 53.56 mV dec −1, which are close to the performance of noble metal catalysts in alkaline condition. The electronic interactions between cobalt and phosphorus are modulated after iron doping, resulting in more positively charged Co, which can promote adsorption and activation of H2 O molecules and will weaken P-Hads bonds formed on the catalyst surfaces. Therefore, Fe0.29 Co0.71 P can optimize the adsorption and desorption of H atoms, and can promote both Volmer and Heyrovsky steps of HER. In addition, the electron density modulation of catalytic sites also improves the OER catalytic performance of Fe0.29 Co0.71 P. The overall water splitting electrolyzer assembled by Fe0.29 Co0.71 P/Ni-foam exhibits a lower cell voltage (1.59 V/10 mA cm −2 ), compared to that (1.61 V/10 mA cm −2 ) of the IrO2 //Pt/C electrolyzer. Graphical abstract: Image 1 Highlights: Fe-doping modulates the surface electron densities and improves the intrinsic activity of catalyst. Fe-doping promotes both Volmer and Heyrovsky steps of HER. Fe-doping can optimize the adsorption energies of the OER intermediates. Reasonable mechanism for the enhanced electrocatalytic activity was well explained.